Lucky Penny - Hirsh, Ananth (Oni Press, 2016)
"If Penny Brighton didn't have bad luck, she'd have no luck at all. She lost her job. And her apartment. In the same day. But it's okay, her friend has a cozy storage unit she can crash in. And there's bound to be career opportunities at the neighborhood laundromat--just look how fast that 12-year-old who runs the place made it to management! Plus, there's this sweet guy at the community center, and maybe Penny can even have a conversation with him without being a total dork. Surely Penny is a capable of becoming an actual responsible adult, and if she can do that her luck's bound to change! Right?"--From back cover.